2013
DOI: 10.1530/joe-13-0477
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of GH resistance in malnutrition

Abstract: States of under-nutrition are characterized by growth hormone resistance. Decreased total energy intake, as well as isolated protein-calorie malnutrition and isolated nutrient deficiencies result in elevated growth hormone levels and low levels of IGF-I. We review various states of malnutrition and a disease state characterized by chronic under-nutrition -- anorexia nervosa -- and discuss possible mechanisms contributing to the state of growth hormone resistance, including FGF-21 and SIRT1. We conclude by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 76 publications
2
86
0
5
Order By: Relevance
“…The authors found a decrease in weight and height standards associated with growth hormone resistance, which improved after shunt surgery. However, they compared the growth-related hormone profiles of malnourished children and healthy children, which could reflect bias since nutritional status may have influenced the studied hormone profiles [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a decrease in weight and height standards associated with growth hormone resistance, which improved after shunt surgery. However, they compared the growth-related hormone profiles of malnourished children and healthy children, which could reflect bias since nutritional status may have influenced the studied hormone profiles [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic undernutrition and protein deficiency result in GH resistance and suppression of IGF-1, in turn leading to stunting [20]. GH induces IGF-1 production in the liver and local tissues and, together with IGF-1-binding protein-3, regulates somatic growth [19].…”
Section: Biomarkers Of Eed Inflammation and Growth Hormone Resistancementioning
confidence: 99%
“…Detection of substantial increases in IGF-1 during therapeutic interventions may be an early indicator for reversal of linear growth faltering. In addition, during periods of protein and caloric deprivation, rising levels of endocrine hormone fibroblast growth factor 21 (FGF21) and protein deacetylase Sirtuin 1 appear to drive GH resistance [20]. Prolonged exposure to high levels of circulating FGF21 disrupts GH signaling and inhibits growth at the bone plate [34-37].…”
Section: Biomarkers Of Eed Inflammation and Growth Hormone Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This state is an acquired GH resistance and an adaptive response to decreased energy intake (4,5). Therefore low IGF-1 levels lead to minimal anabolic effects thus energy can be used for acute needs and slowdown the catabolic process consequently to form aprotective mechanism for survival (6).…”
Section: Introductionmentioning
confidence: 99%